2003
DOI: 10.1136/adc.88.6.482
|View full text |Cite
|
Sign up to set email alerts
|

Growth impairment in the very preterm and cognitive and motor performance at 7 years

Abstract: Background: Infants born of low birth weight often have poor subsequent growth (especially if they were born very preterm), which has been shown to relate to later motor and cognitive development. Aims: To assess a cohort of preterm infants at the age of 7 years for growth, motor, and cognitive measures, and investigate the effects of growth impairment on school performance. Methods: A cohort of 280 children born before 32 completed weeks of gestation were tested, together with 210 term controls. Results: Pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1
14

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(125 citation statements)
references
References 17 publications
9
101
1
14
Order By: Relevance
“…Even though faster growth in infancy and childhood has been shown to benefit neurodevelopment in those born very preterm (<32 weeks) (9)(10)(11)(12), early preterm (<33 weeks) (13), preterm (14), and preterm with extremely low (<1000g) (15)(16)(17)(18) or very low (<1500g) (9,10,(19)(20)(21)(22) birth weight, in some, though not in all studies (23-25), it still remains unknown if faster early growth also benefits neurodevelopment in those born late-preterm. Accordingly, we examined if growth after late-preterm birth predicts neurocognitive functioning, academic performance, or mental health in individuals who were born latepreterm, and who participated in follow-up examinations at 5 and 20 months of corrected age (CA) and 56 months and 25 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Even though faster growth in infancy and childhood has been shown to benefit neurodevelopment in those born very preterm (<32 weeks) (9)(10)(11)(12), early preterm (<33 weeks) (13), preterm (14), and preterm with extremely low (<1000g) (15)(16)(17)(18) or very low (<1500g) (9,10,(19)(20)(21)(22) birth weight, in some, though not in all studies (23-25), it still remains unknown if faster early growth also benefits neurodevelopment in those born late-preterm. Accordingly, we examined if growth after late-preterm birth predicts neurocognitive functioning, academic performance, or mental health in individuals who were born latepreterm, and who participated in follow-up examinations at 5 and 20 months of corrected age (CA) and 56 months and 25 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Os nutrientes do leite materno podem ser insuficientes para o crescimento do PT, sendo necessária a suplementação com proteína e fósforo, melhorando o ganho de peso, a resposta metabólica e a mineralização óssea. 17 Em estudo longitudinal 18 de RNPT avaliados aos 7 anos de idade, observou-se alterações típicas do desenvolvimento e crescimento da criança, tais como menor desempenho motor, menor índice no teste de inteligência, menor perí-metro cefálico (PC) e índice de massa corpórea (IMC), além de déficit de crescimento e desenvolvimento cognitivo em longo prazo e lentidão nas atividades. Estas condições clínicas foram relacionadas diretamente ao fatores nutricionais durante internação e no período pós-natal dos RNMBP e PIG.…”
Section: Discussionunclassified
“…Estas condições clínicas foram relacionadas diretamente ao fatores nutricionais durante internação e no período pós-natal dos RNMBP e PIG. 18 Noutro estudo, Clark et al 19 destacam que prematuridade, baixo peso, sexo, necessidade de suporte ventilatório, presença de ECN e uso de esteróides, estão relacionados com déficit de crescimento no período pós-natal e dificuldade na nutrição. Isto leva a uma dificuldade neurosensorial e um pobre acompanhamento escolar, principalmente aqueles que têm o PC com 8 meses abaixo do esperado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…At 11 y of age, 40% of children born before 26 wk of gestation have been reported to have serious neurocognitive impairment and moderate to severe impairment of neuromotor function, vision and hearing was reported in respectively 10, 9, and 2% of cases (3). Preterm birth and postnatal growth restriction have both been associated with impaired neurodevelopmental outcome (4). However, Franz et al found that only a small percentage of the variability, roughly 3%, of the mental processing composite score was explained by growth (5).…”
mentioning
confidence: 99%